The Role of Environmental Verses in Responding to The Climate Crisis: A Comparative Dialogical Study of the Qur'an and the Bible - Syihabuddin, Muhammad; Nadhifah, Ayu Maun (UIN Sunan Kalijaga Yogyakarta, 2024)
The global climate crisis requires a multidimensional approach, including a religious perspective. The Qur'an and the Bible, as the main sacred texts in the Islamic and Christian traditions, respectively guide man's responsibility to the environment. This study explores how these two sacred texts address environmental issues in the context of climate change. This study aims to analyze and compare environmental teachings in the Qur'an and the Bible, identify similarities and differences in the principles of ecological responsibility, and evaluate their theological and practical implications for climate crisis mitigation efforts. A dialogic-comparative approach is used to analyze relevant verses in the Qur'an and the Bible. The study involved a comparison of texts, identification of major themes, and analysis of theological and applicative differences in environmental contexts. The research found that the Qur'an emphasizes the concept of ‘Khalifah fil’ ardh’ or human leadership over the earth, focusing on resource management and damage prohibition. On the contrary, the Bible teaches the responsibility of caring for the Garden of Eden and showing mercy towards living things. Theological differences include the Qur'anic view of moral reform to address environmental damage and the Qur'anic view of eschatological punishment. Despite differences in the interpretation and application of religious teachings, similarities in the principles of responsibility for God's creation offer a basis for interfaith dialogue and collaboration. The universal values of the Qur'an and the Bible can reinforce collective efforts in climate crisis mitigation while respecting the diversity of religious perspectives. Keywords: Verses in the Qur’an and the Bible, Islam and Christianity, Environmental, Dialog, Evocation.